(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study explores the transformative impact of advanced computer hardware on technical skill development among undergraduate students in Cross River State, Nigeria. With the rapid integration of technology in education, advanced hardware such as high-performance processors, GPUs, and specialized computing devices offers unprecedented opportunities for skill acquisition in fields like programming, data analysis, and digital design. Using a primary data collection method, this research surveyed 400 undergraduate students across three universities in Cross River State, employing a mixed-methods approach with structured questionnaires and semi-structured interviews. Findings reveal a significant positive correlation (r = 0.67, p < 0.05) between access to advanced hardware and proficiency in technical skills, particularly in computer science and engineering disciplines. However, challenges such as inadequate infrastructure, high costs, and limited training hinder optimal utilization. The study underscores the need for strategic investments in hardware resources and faculty development to bridge the digital divide and enhance employability. Recommendations include public-private partnerships to fund hardware upgrades and curriculum integration of hands-on training with advanced systems. This research contributes to the discourse on technology-driven education in developing contexts, emphasizing hardware as a catalyst for skill development.